Spider: managing clinical data of cancer patients treated through a multidisciplinary approach by a palm based system (Italian Journal of Public Health, 2008)
Background: The complexity of modern oncology, based on multi-disciplinary management of cancer patients, results in critical amounts of data, leading to problems in managing and sharing information.Methods: Spider is a multi-user system, based on integrated palm technology, created to facilitate data recording, managing and sharing, through Intra-Internet connection. By palms or PCs, data are collected directly at the place where information is generated. Every health professional can edit, modify and display all of the patient's data according to his/her operational level. A powerful engine enables Spider’s users to create series of cancer patients’ appointments linked to one another by specified time intervals and save them as “Protocols”. Applying a protocol to the patient, the system schedules a wave of appointments and alerts keeping the correlation with time intervals previously specified by specialists. XML technology is integrated with traditional RDBMS technology to build the Electronic Patient File (EPF) updated during each patient’s admission or consultation, including any new diagnostic/therapeutic events and collective decisions. The system automatically produces all clinical documents routinely in use (discharge letters, exams’ requests, etc.).Results: Spider’s different archives include 4387 patients (Prostate, n=849; Lung, n=1596; Rectum, n=1541; Head & Neck, n=291; Cervix, n=110). The EPF includes specific modules: staging, surgery, chemotherapy, hormonotherapy, radiotherapy, toxicity, pathology, follow-up and clinical summary. Spider Hospitalization displays the ward map and important details of patients occupying each single bed.Conclusions: Spider makes data capture easier and accurate. The availability of large amounts of information accelerates outcome analysis and improves cancer research.
Keywords: health information technology; electronic medical record; data sharing; personal digital assistant; multi-disciplinary cancer care